The Effects Of Child Sexual Abuse To The Personality Development Reflected In Jaycee Dugard's A Stolen Life (2011) - Qanita, Farah; , Dr. M. Thoyibi, M.S; , Siti Fatimah, S. Pd., M.Hum (2016)
This research is about child sexual abuse in Jaycee Dugard's A Stolen Life (2011) which is analyzed using Psychosocial Approach proposed by Erik Erikson. The objectives of this study are to find out the way the major character was sexually abused, the major character's responses to the sexuality abuse, and the reasons why the author opened sexual abuse to the public. This research is a qualitative research. The primary data of this research is A Stolen Life (2011) Memoir of Jaycee Dugard. The secondary data are some selected references and material related to the study. There are some conclusions in this research. Child sexual abuse can be done in several ways such as being done as a routine, in contact and non contact abuse. Contact abuse consists of touching, penetration, rape, and masturbation. It is done directly. While non contact abuse is done indirectly like showing pornographic content or in oral. Usually the victim's responses to the sexual abuse are divided into three steps. The earlier step is the first time responses which involve seven feelings; embarrassed, scared, funny, shocked, helpless, innocently strange, and hard to understand. The later step is continuous responses; wanting to be released, expressing sadness through tears, sacrificing, being worried about pregnancy, feeling confused. The last step is final responses when the victim is already adult; rebelling, being patient, thinking positively, begging the perpetrator not to leave the victim, not asking anything much, and feeling relieved after not being sexually abused. There are six reasons why the author opened the sexual abuse to the public such as raising awareness, taking lesson about life, feeling independent, need for sharing, freedom of expression, and positive attitude.